PENELUSURAN BAKAT OLAHRAGA ANAK USIA DINI DI SEKOLAH DASAR - Langgeng Asmoro Budi Mardanto; Rumini (Universitas Negeri Semarang, 2016)
Purpose of this study to know who owned sporting talent early childhood in State Elementary Schools in Cepu Blora Academic Year 2015? Data collection technique used (1) the documentation used to obtain data about the names of members of the population who took the test sport search and photo test execution sport search, (2) questionnaire was used to determine the extent of the role of the teacher penjasorkes related to coaching and talent development participants students, (3) aptitude tests are used to determine the student sport giftedness. The result showed that the Search Talent Sports Childhood In public elementary school in Cepu Blora academic Year 2015 is 33% (38 of 115 children) talented in sports sprint, 13% (15 of 115 children) talented in sports high jump , 16% (18 of 115 children) talented in sports long jump, 14% (16 of 115 children) talented at the sport of distance running, 11% (13 of 115 children) talented in gymnastics, 9% (10 of 115 children ) talented in the sport of table tennis, 4% (5 out of 115 children) talented in sports weightlifting. Based on the results of the research can be concluded that the public elementary school students in Cepu potentials or talents in the field of sport based on test results sport scouting talent search conducted.